Evaluation of the Implementation of Credit Sales System Procedures - Yahumaira, Cut Saidati; Hazmi, Yusri; Alfaiza, Sabila; Kurniawan, Aldo (Westscience Press, 2024)
Credit sales are a method used by many companies to increase sales volume by allowing customers to pay for products or services in stages. In an accounting context, credit sales systems require accurate recording and efficient management to ensure that receivables are collectible and the risk of loss is minimized. This article reviews the basic concepts of credit sales, including accounts receivable, provisions for bad debts, and recording credit sales journals. The benefits of credit sales in accounting include increased sales, better management of receivables, and preparation of accurate financial statements. The main challenges faced are bad debt risk, creditworthiness assessment, and receivables monitoring and collection. Implementation of technology such as ERP systems helps in automating record keeping, credit risk analysis, and more efficient reporting. With proper management and technology support, a credit sales system can be an effective tool in a company's financial strategy, minimizing risks and ensuring healthy cash flow.